Ultra-Thin Porous PDLLA Films Promote Generation, Maintenance, and Viability of Stem Cell Spheroids - Ya An Tsai (Frontiers in Bioengineering and Biotechnology, 2021)
Three-dimensional (3D) culture bridges and minimizes the gap between in vitro and in vivo states of cells and various 3D culture systems have been developed according to different approaches. However, most of these approaches are either complicated to operate, or costive to scale up. Therefore, a simple method for stem cell spheroid formation and preservation was proposed using poly(D,L-lactic acid) porous thin film (porous nanosheet), which were fabricated by a roll-to-roll gravure coating method combining a solvent etching process. The obtained porous nanosheet was less than 200 nm in thickness and had an average pore area of 6.6 μm2 with a porosity of 0.887. It offered a semi-adhesive surface for stem cells to form spheroids and maintained the average spheroid diameter below 100 μm for 5 days. In comparison to the spheroids formed in suspension culture, the porous nanosheets improved cell viability and cell division rate, suggesting the better feasibility to be applied as 3D culture scaffolds.